Combined use of olfactory mucosal mesenchymal stem cells conditioned medium and neural guide conduits promotes nerve regeneration in an ovine model - Alvites, Rui; Lopes, Bruna; Coelho, André; Sousa, Ana Catarina; Sousa, Patrícia; Moreira, Alícia; Rêma, Alexandra; Simões, Maria; Mendonça, Carla; Atayde, Luís; Prada, Justina; Pires, Isabel; et al. (Frontiers in Cell and Developmental Biology, 2025)
IntroductionPeripheral nerve injuries remain a significant clinical challenge, particularly in severe neurotmesis injuries requiring complex therapeutic interventions to restore functionality. This study aimed to evaluate the pro-regenerative potential of combining neural guide conduits with conditioned medium from olfactory mucosa mesenchymal stem cells, compared to gold-standard surgical techniques.MethodsThe study was conducted using a validated ovine model of common peroneal nerve injury. Recovery was assessed over 24 weeks through functional, kinematic, ultrasonographic, and electrophysiological evaluations, complemented by post-mortem nerve stereology and muscle histomorphometry.ResultsAll therapeutic approaches promoted nerve and muscle regeneration, resulting in notable functional and structural improvements. However, irregularities were observed, as neural guide conduits and conditioned medium did not consistently outperform standard techniques. Additionally, recovery often fell short of normal values in the control group.DiscussionThese findings highlight the complexity of peripheral nerve regeneration in challenging surgical scenarios and underscore the translational potential of biomaterials and cell conditioned medium-based therapies. However, the observed irregularities emphasize the need for further research in complex animal models before application in real clinical cases. Such studies are essential to refine therapeutic strategies, address inconsistencies, and establish cell conditioned medium as a viable tool in peripheral nerve regeneration and repair.